Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T16:41:00+01:00
A) 4a+4b=4(a+b)
b) 3x+15y=3(x+5y)
c)7x+14y=7(x+2y)
d)17x²-17=17(x²-1)
e)bc-bd=b(c-d)
f) xy-3x=x(y-3)
g) py-p =p(y-1)
h) 9xy-y=y(9x-1)
i) ab+3b²=b(a+3b)
2010-02-23T16:42:10+01:00
A) 4a+4b= 4(a+b)
b) 3x+15y=3(x+5y)
c)7x+14y=7(x+2y)
d)17x²-17=17(x²-1)
e)bc-bd=b(c-d)
f) xy-3x=x(y-3)
g) py-p =p(y-1)
h) 9xy-y=y(9x-1)
i) ab+3b²= b(a+3b)
2010-02-23T16:42:30+01:00
A)4a+4b=4(a+b)
b) 3x+15y=3(x + 5y)
c)7x+14y= 7(x + 2y)
d)17x²-17=17(x² - 1)
e)bc-bd=b(c-d)
f) xy-3x=x(y - 3)
g) py-p =p(y-1)
h) 9xy-y=y(9x - 1)
i) ab+3b²= b(a+3b)